Novel paradigms for the gut–brain axis during alcohol withdrawal, withdrawal-associated depression, and craving in patients with alcohol use disorder - Vatsalya, Vatsalya; Verster, Joris C.; Sagaram, Manasa; Royer, Amor J.; Hu, Huirong; Parthasarathy, Ranganathan; Schwandt, Melanie L.; Kong, Maiying; Ramchandani, Vijay A.; Feng, Wenke; Agrawal, Ruchita; Zhang, Xiang; et al. (Frontiers in Psychiatry, 2023)
INTRODUCTION: Alcohol use disorder (AUD) patients exhibit domains such as alcohol withdrawal, depression, and craving. The gut-immune response may play a significant role in expressing these AUD domains. This study examined the role of gut-dysfunction, pro-inflammatory cytokines and hormones in the characterization of the AUD domains. METHODS: Forty-eight AUD patients [male (n=34) and female (n=14)] aged 23-63 yrs. were grouped categorically using the Clinical Institute Withdrawal Assessment of Alcohol Scale (CIWA) as clinically significant (CS-CIWA [score>10] [n=22]), and clinically not-significant group (NCS-CIWA [score≤10] [n=26]). Clinical data (CIWA, 90-day timeline followback [TLFB90], and lifetime drinking history [LTDH]) and blood samples (for testing pro-inflammatory cytokines, and hormones, and markers of intestinal permeability) were analyzed. A sub-set of 16 AUD patient were assessed at intake for craving response towards drug-seeking using Penn-Alcohol Craving Score (PACS). RESULTS: CS-CIWA group patients exhibited unique and significantly higher levels of adiponectin and Interleukin (IL)-6 compared to NCS-CIWA. In the CS group, there was significant and high effects of association for withdrawal score with gut-immune markers, (Lipopolysaccharide [LPS], adiponectin, IL-6, and IL-8); and for the withdrawal-associated depression with gut-immune markers (scored using MADRS with LPS, soluble cells of differentiation type 14 [sCD14], IL-6, and IL-8). Craving (assessed by PACS, Penn-Alcohol Craving Scale) was significantly characterized with what could be described as the gut-dysregulation (LBP [Lipopolysaccharide binding protein] and Leptin) and candidate proinflammatory (IL-1β and TNF-α) markers. Such pathway model describes the heavy drinking phenotype, HDD90 (heavy drinking days past 90 days) with even higher effects (R2=0.955, p=0.006) in the AUD patients, who had higher ratings for craving (PACS>5). DISCUSSION: Interaction of gut-dysfunction, cytokines involved in both inflammation and mediating activity constitutes a novel pathophysiological gut-brain axis for withdrawal, and withdrawal-associated depression and craving domains in AUD. AUD patient with reported craving show a significant characterization of the gut-brain axis response for heavy drinking.